O PNAIC e a formação continuada da professora alfabetizadora da rede municipal de ensino de Medianeira - Wagner, Cleonilde Fátima (2017)
In this research, we analyze the proposal of continuing training of the PNAIC to the literacy teachers who work in the 3rd year of Basic Education in the City’s Municipal Education System of Medianeira - Paraná - Brazil. Through the concrete statements of the subjects participating in this training in the city, we try to understand their perceptions about the weaknesses and contributions of the PNAIC to more consistent practices for the promotion of reading and writing teaching. The research focused on the area of Portuguese Language. The study carried out the bibliographical research and the field research. In order to justify the study, we are looking for theorists who have produced studies in Brazil about literacy and language and literacy questions: Mortatti (2000,2008), Soares (1985, 2002, 2003, 2004), Kleiman (1995), Klein 1997), Geraldi (2000,2014), Brotto (2008, 2009, 2013) and others. The basic theorists who base the analyzes are from the theoretical-methodological perspective of language of the Bakhtinian circle, and from the Historical-Cultural perspective of human development based on the studies of Vygotsky (1997). The field research was carried out with the subjects who work alongside the 27 classes of the 3rd Year, and make up a total of 18 teachers, of which 14 are teachers who work in the classrooms and four who work in the Municipal Department of Education as coordinator of pedagogy, and that also act in the orientation of the PNAIC studies in Medianeira. The instrument of data collection was the interview, with audio recordings, following a script with semi-structured questions. The methodology of data processing occurred through the analysis of the discourse present in the subjects' statements, in which we chose the categories of analysis polyphony or plurivocality, theme and dialogism, based on the theoretical-methodological perspective of Bakhtin / Volochínov language [1929] 2014). From the research with the literacy teachers, they demonstrated that the PNAIC offered possibilities for the promotion of teaching and reading, as well as demonstrated who is the subject constituted mediator teacher of Medianeira. It reflects and refracts the continuing formation of the Brazilian context and the data can be used for a broader analysis of the PNAIC.